1988
DOI: 10.1029/ja093ia07p07244
|View full text |Cite
|
Sign up to set email alerts
|

The Jovian aurora: Electron or ion precipitation?

Abstract: High signal‐to‐noise spectra of the Jovian aurora at UV wavelengths obtained using the International Ultraviolet Explorer Observatory (including the brightest Jovian aurora observed to date) are used to study the existence of sulfur and oxygen emissions which would be associated with the precipitation of energetic heavy ions in the upper Jovian atmosphere. Model calculations of heavy ion precipitation and corresponding estimates of the associated sulfur and oxygen UV emissions carried out in the preceding comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The 1295-1330-Å region shows significant discrepancies that can partly be ascribed to the residual presence of the terrestrial OI triplet at 1302.17, 1304.86, and 1306.03Å in the observed spectrum following subtraction of the sky background contribution. The presence of the 1304Å triplet in the jovian auroral spectrum has been a matter of controversy since Waite et al (1998) observed a weak feature in jovian auroral spectra obtained with the spectrograph on board the International Ultraviolet Explorer (IUE) satellite. Trafton et al (1998) analyzed a spectrum obtained between 1282 and 1318Å at 0.5-Å resolution with the Goddard High Resolution Spectrometer (GHRS).…”
Section: Iv2 Second Orbitmentioning
confidence: 99%
“…The 1295-1330-Å region shows significant discrepancies that can partly be ascribed to the residual presence of the terrestrial OI triplet at 1302.17, 1304.86, and 1306.03Å in the observed spectrum following subtraction of the sky background contribution. The presence of the 1304Å triplet in the jovian auroral spectrum has been a matter of controversy since Waite et al (1998) observed a weak feature in jovian auroral spectra obtained with the spectrograph on board the International Ultraviolet Explorer (IUE) satellite. Trafton et al (1998) analyzed a spectrum obtained between 1282 and 1318Å at 0.5-Å resolution with the Goddard High Resolution Spectrometer (GHRS).…”
Section: Iv2 Second Orbitmentioning
confidence: 99%
“…We choose to use the same approach to model the EUV spectra as Grodent et al (2000) have prescribed for the analysis of HST FUV spectra. Our model is a synthesis of (1) the spectral line H 2 Rydberg code for electron impact described by Shemansky (1985) and Ajello et al (1984Ajello et al ( , 1988Ajello et al ( , 1998, (2) the two-stream electron energy degradation transport code derived by Waite et al (1983Waite et al ( , 1988, and (3) the one-dimensional heat conduction, which includes the heating of the atmosphere by the auroral electron precipitation . Grodent et al (2000) recognized that the thermal constraints placed on the upper atmosphere by the H + 3 rovibrational temperatures required soft electron impact with an E o of ∼1 keV to achieve the exospheric temperatures of 700-1300 K. We will show that an even softer electron flux of E o of about 0.1 keV is needed to explain the EUV spectrum.…”
Section: The Modelmentioning
confidence: 99%
“…Auroral activity near Jupiter's north pole has been observed in the FUV by means of rocket experiments, the Voyager ultraviolet spectrometer, and Earth-orbiting telescopes such as the International Ultraviolet Explorer (IUE) satellite [Broadfoot et al, 1981;Durrance et al, 1982;Giles et al, 1976;Rottman et al, 1973;Skinner, 1984;Skinner et al, 1984;Waite et al, 1988]. The IUE is particularly valuable, as its stable orbital position allows consecutive observations sequenced over several hours in order to resolve short time scale variability, while its extraordinary durability has permitted the construction of a data collection spanning more than a decade.…”
Section: Introductionmentioning
confidence: 99%